Revision and Phylogeny of the Genus Phausis (Coleoptera: Lampyridae) with the Description of Three New Species - Hodson, Alicia M.; Branham, Marc A. (Zootaxa, 2024)
An updated revision of the firefly genus Phausis LeConte (Coleoptera: Lampyridae) and the first phylogenetic analysis of all assigned species is herein presented. This treatment includes the description of three new species (Phausis branhami sp. nov., Phausis christineae sp. nov., and Phausis milleri sp. nov.), designation of the neotype of Phausis reticulata (Say, 1825) and lectotype of Phausis inaccensa (LeConte, 1878), descriptions of male aedeagi, and a key to species. A phylogenetic analysis of 13 ingroup taxa and 2 outgroup taxa with a total of 67 morphological characters was also conducted. The resulting phylogenetic hypothesis supports the monophyly of Phausis as presently defined and the evolution of adult bioluminescence as a derived character. A discussion of whether Lamprohiza splendidula (Linnaeus, 1767) should be assigned to Phausis LeConte is also presented.